Analyzing the Impact of an 8-Week Structured Physical Activity Program on Health-Related Fitness in Bhutanese Seventh-Grade Students - Gayley Lhendup; Pufa Savagpun; Arphat Tiaotrakul (Physical Education Theory and Methodology)
Objectives. This study aimed to evaluate the impact of an 8-week physical activity program (PAP) on health-related fitness (HRF) components of seventh graders in Bhutan. Its emphasis areas included assessing the program’s effects on cardiorespiratory endurance, muscular strength, muscular endurance, flexibility, and body composition.